1978
DOI: 10.1016/0304-3959(78)90037-4
|View full text |Cite
|
Sign up to set email alerts
|

Endorphins in chronic pain. I. Differences in CSF endorphin levels between organic and psychogenic pain syndromes

Abstract: A series of 37 patients with chronic pain was investigated with regard to neurologic and psychiatric variables. Twenty of the patients were classified as having mainly organic (= somatogenic) pain syndromes while 17 patients were rather suffering from psychogenic pain syndromes. Samples of lumbar cerebrospinal fluid (CSF) were obtained from the patients and analyzed for the presence of opiate receptor-active material, here called endorphins. Patients classified as having mainly organic pain syndromes were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(38 citation statements)
references
References 19 publications
4
33
0
1
Order By: Relevance
“…[19]. Decreased levels of f-END detected in the cerebrospinal fluid of patients suffering from chronic arthritis or chronic low back pain [20] led to the findings in chronic pain models that peripheral lesions can induce important changes in brain concentrations of opioid peptides involved in the modulation of pain [9]. Similar changes of opioid peptide levels in the central nervous system may be induced by neuropharmacological treatment of experimental animals [21,22].…”
Section: Methodsmentioning
confidence: 68%
“…[19]. Decreased levels of f-END detected in the cerebrospinal fluid of patients suffering from chronic arthritis or chronic low back pain [20] led to the findings in chronic pain models that peripheral lesions can induce important changes in brain concentrations of opioid peptides involved in the modulation of pain [9]. Similar changes of opioid peptide levels in the central nervous system may be induced by neuropharmacological treatment of experimental animals [21,22].…”
Section: Methodsmentioning
confidence: 68%
“…However, other studies of adults have failed to confirm this age-effect on CSF-BE [4,8,167]. All in all, the balance of evidence does not favour a simple confounding effect of age on CSF-BE.…”
Section: Agementioning
confidence: 91%
“…Already in 1978, Almay et al reported that levels of unspecific "endorphins" were low in the CSF of patients with predominantly "neuralgic" pain, compared both to patients with what was labelled "psychogenic" pain and to healthy controls [4]. Also, in 1988, Tonelli et al found low CSF-BE in patients scheduled for Spinal Cord Stimulation (SCS), compared to historic controls [238].…”
Section: Neuropeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity in the endorphin systems is altered in chronic pain states (1,18), and the endorphins seem to have a physiological role in pain perception (3,11).…”
Section: Introductionmentioning
confidence: 99%